Which of the following expressions does not mean the same as the other three?

x - (-17) = x + 17 does not mean the same as the other three. x - 17 = x - 17 x + (-17) = x - 17 x - (-17) = x + 17 - 17 + x = x - 17

Question

Asked 9/10/2014 9:31:30 PM

Updated 9/10/2014 11:42:22 PM

1 Answer/Comment

Edited by jeifunk [9/10/2014 11:41:48 PM]

Rating

8

x - (-17) = x + 17 does not mean the same as the other three.

x - 17 = x - 17

x + (-17) = x - 17

x - (-17) = x + 17

- 17 + x = x - 17

x - 17 = x - 17

x + (-17) = x - 17

x - (-17) = x + 17

- 17 + x = x - 17

Added 9/10/2014 11:42:22 PM

This answer has been confirmed as correct and helpful.

Solve -5 + w/3 = -1.
12
-12
2
-2

Question

Updated 9/4/2014 9:21:47 PM

1 Answer/Comment

-5 + w/3 = -1

w/3 = -1 + 5

w/3 = 4

w = 4 * 3

w = 12

w/3 = -1 + 5

w/3 = 4

w = 4 * 3

w = 12

Added 9/4/2014 9:21:47 PM

This answer has been confirmed as correct and helpful.

Solve 24 - 3x = -27.

Question

Updated 9/4/2014 10:06:05 PM

1 Answer/Comment

24 - 3x = -27

-3x + 24 = - 27

-3x = -27 - 24

-3x = -51

x = -51/-3

x = 17

-3x + 24 = - 27

-3x = -27 - 24

-3x = -51

x = -51/-3

x = 17

Added 9/4/2014 10:06:05 PM

This answer has been confirmed as correct and helpful.

All of the following expressions have the same value except _____.
(-2)(4)
(2)(-4)
-16 ÷ 2
-16 ÷ -2

Question

Updated 9/10/2014 7:44:49 PM

1 Answer/Comment

All of the following expressions have the same value except -16 ÷ -2.

(-2)(4) = -8; (2)(-4) = -8; -16 ÷ 2 = -8; -16 ÷ -2 = 8

(-2)(4) = -8; (2)(-4) = -8; -16 ÷ 2 = -8; -16 ÷ -2 = 8

Added 9/10/2014 7:44:49 PM

This answer has been confirmed as correct and helpful.

Find the value of -7 + 3(-12) ÷ (-3).
-16
-19
-40
5

Question

Updated 9/11/2014 12:02:50 AM

1 Answer/Comment

-7 + 3(-12) ÷ (-3)

= -7 + -36/-3

= -7 + 12

= 5

= -7 + -36/-3

= -7 + 12

= 5

Added 9/11/2014 12:02:50 AM

This answer has been confirmed as correct and helpful.

32,793,308

questions answered

There are no comments.